MORAL FILM MESSAGE ON WEB SERIES TEMAN KE SURGA - Debbie Pradhita; Panji Dwi Ashrianto; Yenni Sri Utami (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2019)
Nowadays, the phenomenon of religious-themed films is increasingly emerging in Indonesia, because Indonesia is a country with the largest Muslim population in the world, making it one of the target markets for religious nuances. Film web series Teman ke Surga are interesting as learning media for religious moral values in the midst of the rise of television films, most of which are not in accordance with the teachings of Islam. The formulation of the problem in this research is how is the perception of the public in the Yogyakarta Regional Yuk Ngaji community towards the moral message in the web series film